Wave reflections and global arterial compliance during normal human pregnancy. Issue 24 (21st December 2018) - Rodriguez, Claudia; Chi, Yueh‐Yun; Chiu, Kuei‐Hsun; Zhai, Xiaoman; Lingis, Melissa; Williams, Robert Stan; Rhoton‐Vlasak, Alice; Nichols, Wilmer W.; Petersen, John W.; Segal, Mark S.; Conrad, Kirk P.; Mohandas, Rajesh
Abstract: Profound changes occur in the maternal circulation during pregnancy. Routine measures of arterial function – central systolic pressure (CSP) and augmentation index (AIx) – decline during normal human pregnancy. The objectives of this study were twofold: (1) explore wave reflection indices besides CSP and AIx that are not routinely reported, if at all, during normal human pregnancy; and (2) compare wave reflection indices and global arterial compliance (gAC) obtained from carotid artery pressure waveforms (CAPW) as a surrogate for aortic pressure waveforms (AOPW) versus AOPW synthesized from radial artery pressure waveforms (RAPW) using a generalized transfer function. To our knowledge, a comparison of these two methods has not been previously evaluated in the context of pregnancy. Ten healthy women with normal singleton pregnancies were studied using applanation tonometry (SphygmoCor) at pre‐conception, and then during 10–12 and 33–35 gestational weeks. CSP and AIx declined, and gAC increased during pregnancy as previously reported. As a consequence of the rise in gAC, the return of reflected waves of lesser magnitude from peripheral reflection sites to the aorta was delayed that, in turn, reduced systolic duration of reflected waves, augmentation index, central systolic pressure, LV wasted energy due to reflected waves, and increased brachial‐central pulse pressure. For several wave reflection indices, those derived from CAPW as a surrogate for AOPW versus RAPW using a generalized transfer function registered greater gestational increases of arterial compliance. This discordance may reflect imprecision of the generalized transfer function for some waveform parameters, though potential divergence of carotid artery and aortic pressure waveforms during pregnancy cannot be excluded. Abstract : The objectives of this study were twofold: (1) explore wave reflection indices besides CSP and AIx that are not routinely reported, if at all, during normal human pregnancy; and (2) compare wave reflection indices and global arterial compliance (gAC) obtained from carotid artery pressure waveforms (CAPW) as a surrogate for aortic pressure waveforms (AOPW) versus AOPW synthesized from radial artery pressure waveforms (RAPW) using a generalized transfer function. Ten healthy women with normal singleton pregnancies were studied using applanation tonometry (SphygmoCor) at pre‐conception, and then during 10–12 and 33–35 gestational weeks.